Distance-Based Sampling Methods for Assessing the Ecological Effects of Offshore Wind Farms: Synthesis and Application to Fisheries Resource Studies - Methratta, Elizabeth T. (Frontiers in Marine Science, 2021)
Renewable energy, sustainable seafood, and a healthy marine ecosystem are integral elements of a sustainable blue economy. The rapid global advancement of offshore wind coupled with its potential to affect marine life compels an urgent need for robust methodologies to assess the impacts of this industry on fisheries resource species. Basic Before-After-Control-Impact (BACI) and Control-Impact (CI) designs are the most common experimental designs used to study the effects of offshore wind development on fisheries resources. These designs do not account for spatial heterogeneity which presents a challenge because empirical evidence shows that impact gradients occur at wind farms, with larger effect sizes close to turbine foundations that attenuate with increasing distance. Combining the before-after sampling design with distance-based methods could provide a powerful approach for characterizing both the spatial and temporal variance associated with wind development. Toward enhancing future monitoring designs for fisheries resource species at offshore wind farms, this paper aims to: (1) examine distance-based sampling methods that have been or could potentially be used to study impacts on fisheries resources at offshore wind farms including distance-stratified BACI, distance-stratified CI, Before-After-Gradient (BAG), and After-Gradient (AG) methods; (2) synthesize the methods and findings of studies conducted to date that have used distance-based methods to examine ecological impacts of offshore wind development for benthic macroinvertebrates, finfish, birds, and small mammals; (3) examine some of the central methodological elements and issues to consider in developing distance-based impact studies; and (4) offer recommendations for how to incorporate distance-based sampling methods into monitoring plans at offshore wind farms.